Poster: We Are Well: Our well-being superpower (leaves) ... - Burke, Geraldine; Pettengell, Priscilla; Hanger, Chris (Monash University, 2023)
The poster, We Are Well: Our well-being superpower (leaves) is part of a suite of posters that document the 'We Are Well: Intergenerational art-moving-well-being' project. It showcases a series of gum leaves harvested from a local tree and drawn on to depict well-being assets through words and pattern. Poster text: Look what we bring to the learning. Look what I bring to the group. We are artists/researchers/teachers with amazing superpowers to share. Poster Authors: Geraldine Burke, Priscilla Pettengell, Chris Hanger Photography: Geraldine Burke, Melanie Attard, Aislinn Lalor, Megan Adams, Chris Hanger Project Acknowledgments: The We Are Well: Intergenerational art-moving-well-being research team Dr Geraldine Burke, Assoc Prof Megan Adams, Assoc Prof Laura Alfrey, Dr Aislinn Lalor, Prof Keith Hill, and Priscilla Pettengell with artists : Nikki Browne, Bidjara artist and educator, and First Nations Learning and Programs Manager, McClelland Sculpture Park and Gallery, Aunty Karan Kent, Bidjara and local ...